DPOC na população sob vigilância pela Rede Médicos Sentinela de 2007 a 2009 - Sousa, Jaime Correia de (2012)
Objectives: To determine the number of chronic obstructive pulmonary disease (COPD)-related consultations among patients registered in the Portuguese Sentinel Practice Network (PSPN) between 2007 and 2009, to calculate the reasons for visits related to COPD, to estimate the incidence of COPD, and to characterize COPD-related therapy. Study design: Dynamic cohort. Setting: Muticentric. Participants: Patients = 45 years old from the lists of general practitioners in the PSPN between 2007 and 2009. Methods: A study of COPD-related consultations over a three-year period, reporting the frequency, the reasons for consultation and treatments was conducted. The estimated incidence rate of COPD was calculated and extrapolated to the Portuguese population. The chi-square test to compare proportions and the t-student test for comparison of means were used. Results: During the study period, the population under observation was 106,953 individuals and 2,916 consultations related to COPD were reported. Of these, 62.5% were for males. New cases of COPD were reported in 173 persons = 45 years old, of which 59.5% were males, with a median age of 66.9 years,. No significant age difference was found between genders. We calculated an annual incidence rate of 161.8/100,000 (95% CI: 139.4-187.7), higher in men. The reasons for consulting were renewal of prescriptions (61.9%), follow-up appointments (22.9%) and exacerbation of symptoms (15.6%). Medication was prescribed in 87.3% of consultations, mainly for inhaled bronchodilators, including anti-cholinergic drugs (25.1%) and ß adrenergic agonists (20.3%). Conclusions: There were more COPD-related visits and a higher incidence rate of COPD for men, though the value observed was lower than expected. This was probably due to under-diagnosis or to the fact that patients who do not attend Primary Health Care clinics were excluded. The prescription pattern found was consistent with the recommendations of the Global Initiative for Chronic Obstructive Lung Disease. Objetivos: Quantificar as consultas relacionadas com DPOC dos utentes inscritos em Médicos Sentinela (MS) entre 2007 e 2009, avaliar os principais motivos de consulta relacionadas com DPOC e estimar a incidência da doença nessa população e caraterizar a terapêutica utilizada na DPOC pelos MS. Tipo de estudo: Coorte dinâmica. Local: Multicêntrico. População: Utentes com idade igual ou superior a 45 anos inscritos nas listas dos MS de 2007 a 2009. Métodos: Análise das consultas relacionadas com DPOC durante o período referido quanto à frequência e motivos de consulta e ao tratamento farmacológico instituído. Cálculo da taxa de incidência e extrapolação para a população portuguesa. Utilização dos testes qui-quadrado (comparação de proporções) e t-student (comparação de médias). Resultados: No conjunto dos três anos, a população sob observação na Rede Sentinela foi de 106.953 indivíduos. Foram notificadas 2.916 consultas relacionadas com DPOC (62,5% no sexo masculino), e 173 novos casos com idade igual ou superior a 45 anos (59,5% no sexo masculino), com média de idades de 66,9 anos, sem diferença significativa relativamente à idade entre os sexos. Calculou-se uma taxa de incidência média anual de 161,8/100.000 (IC 95%: 139,4-187,7/100.000), superior no sexo masculino. Os principais motivos de consulta notificados foram: renovação de medicação (61,9%), consultas de seguimento (22,9%) e exacerbação de sintomas (15,6%). Foi prescrita medicação em 87,3% das consultas, com predomínio de fármacos broncodilatadores de uso inalatório: anticolinérgicos (25,1%) e ß-adrenérgicos (20,3%). Conclusões: A frequência de consultas e taxa de incidência foram maiores no sexo masculino, estando o valor obtido desta última aquém do esperado, presumivelmente pelo subdiagnóstico da doença e pela exclusão dos doentes que não frequentam as consultas dos CSP. O padrão de prescrição foi concordante com as recomendações da Global Initiative for Chronic Obstructive Lung Disease.